2018
DOI: 10.1016/j.chaos.2018.09.023
|View full text |Cite
|
Sign up to set email alerts
|

A new mathematical formulation for a phase change problem with a memory flux

Abstract: A mathematical formulation for a one-phase change problem in a form of Stefan problem with a memory flux is obtained. The hypothesis that the integral of weighted backward fluxes is proportional to the gradient of the temperature is considered. The model that arises involves fractional derivatives with respect to time both in the sense of Caputo and of Riemann-Liouville. An integral relation for the free boundary, which is equivalent to the "fractional Stefan condition", is also obtained.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Finally, we notice that the assumptions in [28] (see the third problem discussed in section 2) do not imply those considered here. In fact: The (nonlocal) heat flux (2.3) in combination with a classical energy conservation law in the liquid phase yields…”
Section: A Heuristic Approach Leading To a Time-fractional Stefan Promentioning
confidence: 89%
See 3 more Smart Citations
“…Finally, we notice that the assumptions in [28] (see the third problem discussed in section 2) do not imply those considered here. In fact: The (nonlocal) heat flux (2.3) in combination with a classical energy conservation law in the liquid phase yields…”
Section: A Heuristic Approach Leading To a Time-fractional Stefan Promentioning
confidence: 89%
“…0 < x < s(t), t > 0, which in general differs from (3.2) since, as pointed out in [28], we cannot interchange the first integral operator with the classical spacial derivative in the right-hand side due to the loss of differentiability of the heat fluxq along the interface.…”
Section: A Heuristic Approach Leading To a Time-fractional Stefan Promentioning
confidence: 99%
See 2 more Smart Citations
“…In papers, 6‐10 the authors discussed other possible formulations of time‐fractional Stefan problem and compare the formulas for special solutions. In paper, 11 there is shown that the time‐fractional sharp‐interphase model obtained in Falcini et al 1 is not a consequence of the assumption (). Moreover, the authors obtained a new model based on ().…”
Section: Introductionmentioning
confidence: 91%